Isoetes nana, a new species from the coastal mountains of southeastern Brazil - Jovani Pereira; Thomas Stutzel; Christian Schulz (PhytoKeys, 2017)
Isoetes nana, a new species from the coastal mountains of southeastern Brazil (Serra de Itatiaia), is described, illustrated and compared to similar species. This species can be distinguished from similar species by a set of characters that include 5–15 small erect leaves reaching only up to 3.5cm long, megaspores rugulate (rarely laevigate or obscurely cristate) and microspores sparsely echinate. We include a key to identify this new species and spore images for all species that are discussed in this study. Isoetes nana is known only from the type locality, where it was reported to occur in small ponds on rocky outcrops at high elevations. We suggest it should be classified as a data deficient species based on the IUCN criteria.